Pengaruh Motivasi, Pengalaman Kerja, dan Lingkungan Kerja terhadap Prestasi Kerja Guru SMK Muhammadiyah 1 Ngoro Jombang - Amirul Fahmi; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2016)
The development of the world of education is now so rapidly advanced that teachers are required to create learners who can survive in the environment and the world of work, this is offset by Soft Skill and Hard Skill that can be implemented in the real world of work. One of the problems that exist in the world of education is the low achievement of teachers this can affect student achievement. Therefore, improving the quality of education, teachers are required to improve the ability to teach and in providing materials supported by props so that teachers will get feedback from the results of teaching. The purpose of this study is to know and analyze the influence of motivation, work experience and work environment partially and simultaneously to the work performance of teachers Smk Muhammadiyah 1 Ngoro JombangApproach in this research is quantitative approach of causality, type of data used is quantitative data type. Data collection techniques used in this study using questionnaires. Population and sample in this research is 28 staff of teacher at SMK Muhammadiyah 1 Ngoro. Data analysis techniques using Multiple Linear Regrations.The Partialy results showed that the motivation has a negative effect on work performance. work experience has a positive effect on work performance. The work environment has a negative effect on work performance. And simultanly test results show that the motivation, work experience, work environment does not influence jointly to work performance .